2016
DOI: 10.1038/srep30768
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of three Bifidobacterium species isolated from the calf gastrointestinal tract

Abstract: Ruminant animals contribute significantly to the global value of agriculture and rely on a complex microbial community for efficient digestion. However, little is known of how this microbial-host relationship develops and is maintained. To begin to address this, we have determined the ability of three Bifidobacterium species isolated from the faeces of newborn calves to grow on carbohydrates typical of a newborn ruminant diet. Genome sequences have been determined for these bacteria with analysis of the genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…It begs the question whether the ruminant gastrointestinal tract, with its complex fermentation system, activates generic efflux pump mechanisms that may provide the WT population with enhanced ability to withstand the action of antimicrobials in the absence of specific acquired resistance mechanisms. The importance of efflux pumps as a common detoxification mechanism employed by bacteria in the gastrointestinal intestinal tract of ruminants has been demonstrated [41], as has their physiological role during the anaerobic adaptation of facultatively aerobic bacteria [42]. Follow-up through in vitro or in silico analysis of ruminant isolates may shed light on the mechanism underpinning this hypothesis and the phenotypic observations reported here.…”
Section: Plos Onementioning
confidence: 70%
“…It begs the question whether the ruminant gastrointestinal tract, with its complex fermentation system, activates generic efflux pump mechanisms that may provide the WT population with enhanced ability to withstand the action of antimicrobials in the absence of specific acquired resistance mechanisms. The importance of efflux pumps as a common detoxification mechanism employed by bacteria in the gastrointestinal intestinal tract of ruminants has been demonstrated [41], as has their physiological role during the anaerobic adaptation of facultatively aerobic bacteria [42]. Follow-up through in vitro or in silico analysis of ruminant isolates may shed light on the mechanism underpinning this hypothesis and the phenotypic observations reported here.…”
Section: Plos Onementioning
confidence: 70%
“…The resulting consensus tree is in concordance with a previous one published by O’Callaghan and coworkers [ 22 ]. Group B includes representatives of the subspecies suis taxonomic group, which comprises strains isolated from pigs and from a calf [ 17 , 19 ]. A new subspecies, B. longum ssp .…”
Section: Discussionmentioning
confidence: 99%
“…The B. longum taxon currently recognizes four subspecies: longum , infantis , suis and suillum [ 17 , 18 ]. Isolates of the latter two subspecies are of animal origin [ 17 , 19 ], while the former two are considered to be characteristic of the human gut microbiota. Genomic and functional studies have indicated that B. longum ssp.…”
Section: Introductionmentioning
confidence: 99%
“…The use of animals, including welfare, husbandry, experimental procedures, and the collection of samples used for this study, was approved by the Grasslands Animal Ethics Committee (Animal Ethics application 13518, Grasslands, Palmerston North, New Zealand) and performed in accordance with approved institutional and regulatory guidelines. Faecal and recto-anal mucosal swab (RAMS) samples were obtained from 23 calves aged 15 to 16 days old as part of an experiment to investigate the role of two bifidobacterial strains, Bifidobacterium longum AGR2137 and Bifidobacterium pseudolongum AGR2145 50 on animal growth and performance. Probiotic strains were prepared fresh daily as described previously 50 and orally dosed (approximately 10 10 colony forming units per animal per day) to 12 (10 male, 2 female) individually penned calves that were housed in a separate room from 12 (10 male, 2 female) control animals.…”
Section: Methodsmentioning
confidence: 99%